Best Answer

It is an arithmetic series with initial number as 7 and an increment of -5, hence the nth term in general = (7 - 5 x n). You can verify this

0th term = (7 - 5 x 0) = 7

1st term = (7 - 5 x 1) = 2

2nd term = (7 - 5 x 2) = -3

...

...

14th term = (7 - 5 x 14) = -63

Q: What is the 14th term in the sequence 7 2 -3 -8 -13?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

They are: nth term = 6n-4 and the 14th term is 80

1, 1, 2, 3, 5, 8, 13, 21, ...Restate the question: What are the terms of the Fibonacci sequence?The Fibonacci sequence is formed by beginning with the first two terms both equal to one. From there on, each term is found by adding the two previous terms:1+1=2, 1+2=3, 2+3=5, 3+5=8, 5+8=13, 8+13=21, ...

Let n (i) = the term number of each term in the sequence., with (i) going from 1-6 E.g term number 1 (n (1) ) is 3. n(2)= -7 etc... Therefore n(i) for odd terms in the sequence is n (i)= (n (i -2)th term +1). For even terms in the sequence, n(i)= (n (i - 2)th term -3).

This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term

Assuming each term is 3 MORE than the previous term t(n) = -13 + 3*n where n = 1, 2, 3, ...

Related questions

They are: nth term = 6n-4 and the 14th term is 80

13 This is because each term of the sequence is determined by adding the 2 previous terms of the sequence. This particular sequence is called the Fibonacci Sequence, and has special properties. See related link.

The general term of the sequence 2, 4, 2, 4, 2, 4 is repeating number sequence.

1, 1, 2, 3, 5, 8, 13, 21, ...Restate the question: What are the terms of the Fibonacci sequence?The Fibonacci sequence is formed by beginning with the first two terms both equal to one. From there on, each term is found by adding the two previous terms:1+1=2, 1+2=3, 2+3=5, 3+5=8, 5+8=13, 8+13=21, ...

Let n (i) = the term number of each term in the sequence., with (i) going from 1-6 E.g term number 1 (n (1) ) is 3. n(2)= -7 etc... Therefore n(i) for odd terms in the sequence is n (i)= (n (i -2)th term +1). For even terms in the sequence, n(i)= (n (i - 2)th term -3).

It is: 1 1 2 3 5 8 13 and 21 which is the 8th term

The general term for the sequence 0, 1, 1, 2, 2, 3, 3 is infinite sequence.

It Depends if the sequence was 5,7,9,11,13 the term to term rule wud be start at 5 and add 2 each time till you get 13. Hope this helps! :D

This is the Fibonacci sequence, where the number is the sum of the two preceding numbers. The nth term is the (n-1)th term added to (n-2)th term

Assuming each term is 3 MORE than the previous term t(n) = -13 + 3*n where n = 1, 2, 3, ...

recursive rule: term(n+1) = term(n) + (n) also, n starts at 0 and term(1)=3 term(1) = 3 ; (n=0) term(2) = term(1) + (1) = 4 term(3) = term(2) + (2) = 6 term(4) = term(3) + (3) = 9 term(5) = term(4) + (4) = 13 . . .

Any number you like.If you fit a linear equation, Un = 24 - 11n then the 6th term is 42.However,Vn = (-29x4 + 290x3 - 1015x2 + 790x + 744)/60 gives the sequence 13, 2, -9, -20, -42.6, and -100Wn = (7x4 - 70x3 + 245x2 - 570x + 648)/20 gives the sequence 13, 2, -9, -20, -22.6, and 0whileXn = (71x4 - 710x3 + 2485x2 - 4210x + 3144)/60 gives the sequence 13, 2, -9, -20, -2.6, and 100By suitable choice of polynomial, any number at all can be in sixth place.